2022
DOI: 10.3389/fimmu.2022.835103
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chemotherapy Combined With Chidamide Versus Chemotherapy in the Frontline Treatment for Peripheral T-Cell Lymphoma

Abstract: BackgroundPeripheral T-cell lymphoma (PTCL) is featured with a poor survival outcome. China has approved chidamide, an oral novel histone deacetylase inhibitor, for patients diagnosed with relapsed or refractory PTCL.ObjectiveWe compared the benefit of traditional chemotherapy alone and a combination of chidamide and traditional chemotherapy against newly diagnosed PTCL. Prognostic factors related to progression and survival in patients diagnosed with untreated PTCL were also investigated.Methods104 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…No significant increase in grade ≥ 3 adverse events or the incidence of EBV/HBV reactivation was observed. Since the IPI was found to have prognostic significance in the survival of the patients with newly diagnosed PTCL, and the choice of chemotherapy regimen may make a difference to the survival outcome, a possible explanation for the non-significantly different survival outcome may be attributed to the less benefit of C-CHOEP in patients with low IPI, which was consistent with other studies conducted in Chinese patients [25,26].…”
Section: Discussionsupporting
confidence: 87%
“…No significant increase in grade ≥ 3 adverse events or the incidence of EBV/HBV reactivation was observed. Since the IPI was found to have prognostic significance in the survival of the patients with newly diagnosed PTCL, and the choice of chemotherapy regimen may make a difference to the survival outcome, a possible explanation for the non-significantly different survival outcome may be attributed to the less benefit of C-CHOEP in patients with low IPI, which was consistent with other studies conducted in Chinese patients [25,26].…”
Section: Discussionsupporting
confidence: 87%
“…Qingqing Cai et al compared the e cacy and safety of chemotherapy combined with chidamide (ChT + C) versus chemotherapy (ChT) in newly diagnosed PTCLs, they found that patients in ChT + C group had superior PFS compared with patients in ChT group, and the bene ts of ChT + C are higher for patients with high IPI scores, there was no signi cantly statistical difference observed between the two groups in OS. It is worth noting that, the median duration of response in ChT group and ChT + C group were 10.0 months and 14.0 months, with no signi cant difference (P = 0.135) [23].…”
Section: Discussionmentioning
confidence: 85%
“…Rh-endostatin 8.2 [34] 1.83 1.02 0.39 0.22 Erlotinib 9.7 [35] 2.37 0.3 0.5 0.07 Everolimus 4.9 [36] 1.29 0.48 0.27 0.11 Chidamide 8.5 [37] 2.78 1.77 0.59 0.39 Apatinib 12 [38] 5.49 2.1 1.16 0.46 Nimotuzumab 7.29 [39] 3.51 1.06 0.74 0.23 Sunitinib 5.6 [40] 2.77 0.66 0.59 0.14 Dasatinib 4 [41] 2.06 0.38 0.44 0.08 Nilotinib 12 [42] 7.65 1.73 1.62 0.38 Sorafenib 12 [43] 7.97 1.3 1.69 0.28 Bevacizumab 11.2 [44] 8.25 1.7 1.75 0.37 Bortezomib 12 [45] 12…”
Section: Affordabilitymentioning
confidence: 99%